The Philippine Archipelago - Boquet, Yves. (Cham Springer International Publishing Imprint: Springer, 2017)
This book presents an updated view of the Philippines, focusing on thematic issues rather than a description region by region. Topics include typhoons, population growth, economic difficulties, agrarian reform, migration as an economic strategy, the growth of Manila, the Muslim question in Mindanao, the South China Sea tensions with China and the challenges of risk, vulnerability and sustainable development.
PART 1 - Land, history and people -- Chapter 1 7107 islands -- Chapter 2 A tropical archipelago -- Chapter 3 The Spanish creation of the Philippines: the birth of a nation -- Chapter 4 From US colony to independent country: the construction of a State -- Chapter 5 100 million Filipinos -- Chapter 6 The diversity of the Philippine population -- Chapter 7 Emerging tiger ? The paradoxes of the Philippine economy -- Chapter 8 Farm productions and rural landscapes -- Chapter 9 The Philippine agriculture : weaknesses and controversies -- Chapter 10 The use and abuse of sea resources -- Chapter 11 Industry vs. Services -- Chapter 12 Global Pinoys: the archipelago of migration -- PART 3 - Regional organization and spatial planning -- Chapter 13 The spatial structure of the Philippines: urbanization and regional inequalities -- Chapter 14 Transportation in the Philippines -- Chapter 15 The growth of Greater Manila -- Chapter 16 Managing Metro Manila -- Chapter 17 Regional development policies in the Philippines -- PART 4 - Challenges for the Philippines -- Chapter 18 Towards a Bangsamoro in Mindanao ? -- Chapter 19 South China Sea or West Philippine Sea ? -- Chapter 20 It's more fun in the Philippines ? The challenges of tourism in the Philippines -- Chapter 21 Environmental challenges in the Philippines -- Conclusion: Towards sustainable development in the Philippines?
Description based on publisher-supplied MARC data.
Keywords: Asia-Politics and government; Climate change; Ethnology-Asia.; Physical geography; Southeast Asia-History.; Asian Politics